Leisure societies: some cultural adaptations (Journal of Parents and Teachers, 2014)
The weekend has become a pleasant “end” by itself, full of hedonistic content. This free time provides a kind of freedom that allows the person to develop and socialize with others. However, the weekend is becoming more and more mythical. This has many elements in its favor such as commercial interest for the leisure industry. In addition, this has an impact on children and young people who learn from what they see. Adults lay the foundations of the social system and children put into practice what they have learned, this makes everyone responsible for the socialization process of others. However, socioeconomic changes are making children grow faster and behave in ways not appropriate to their age.
Keywords: Leisure; consumption; adults; children; youth; work; rest; weekend